Letter from the Nuclear Security Women Editors - Lindsey K Gehrig; Kathleen A Doty (International Journal of Nuclear Security, 2023)
Letter from the Nuclear Security Women Editors for the IJNS and NSW Special Issue: Women in Nuclear Security